Managing Chronic Nonspecific Low Back Pain With a Sensorimotor Retraining Approach: Exploratory Multiple-Baseline Study of 3 Participants. - Wand, Benedict M.; O'Connell, Neil E.; Di Pietro, Flavia; Bulsara, Max (Physical Therapy, 2011)
Background. Current approaches to the management of chronic nonspecific low back pain (CNSLBP) have shown limited effectiveness. It appears that disruption of cortical structure and function is a feature of CNSLBP and that these changes may contribute to current treatment failures. Sensorimotor retraining approaches have been shown to be effective in the management of other long-standing pain problems that are characterized by cortical dysfunction. Similar treatments may be an option for people with CNSLBP.Objective. The objectives of this study were to describe the effects of participation in a graded sensorimotor retraining program on pain intensity, interference of pain with daily life (pain interference), and self-reported disability and to evaluate the safety of the program. Design. A multiple-baseline, replicated, single-case design was used for this study. Methods. Three people with disabling CNSLBP were assessed weekly during a no-treatment baseline period. Each person then participated in a graded sensorimotor retraining program for a minimum of 10 weeks, during which clinical status was assessed weekly. Data collection continued weekly for 1 month after the end of formal treatment. Results. Pain intensity, pain interference, and disability all were reduced, and the improvements were maintained throughout the follow-up period. No adverse reactions to treatment were reported. Limitations. The findings are preliminary and were based on a single-case design. The observed improvements in clinical status may have been attributable to the effects of factors other than treatment, such as the effect of time and other, nonspecific effects. Conclusions. Positive outcomes were reported for 3 participants with CNSLBP after the completion of a graded sensorimotor retraining program. However, the findings are only preliminary and require replication with more-robust study designs.